2006
DOI: 10.1159/000093791
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of the Left and Right Coronary Arteries of Swine

Abstract: Coronary artery disease is one of the leading causes of myocardial infarction. Despite the predominant role of the coronary arteries in the induction of myocardial infarction, the precise contribution of each artery to this process is not well established. The present work evaluates the histological characteristics and functional properties of the left (LCA) and right (RCA) coronary arteries in swine in order to establish if the arteries are differentially regulated. To investigate this possibility, concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The potency order observed was: 5-HT 1 5-CT 1 sumatriptan, similar to that reported in the literature [16,17] . It was reported [17,18] that the ability of 5-HT to constrict rabbit coronary arteries is mediated by both 5-HT 1B and 5-HT 2A receptors. Our data also indicate that a mixed receptor population mediates contractile responses to 5-HT, including 5-HT 1B and 5-HT 2A receptors.…”
Section: Discussionmentioning
confidence: 97%
“…The potency order observed was: 5-HT 1 5-CT 1 sumatriptan, similar to that reported in the literature [16,17] . It was reported [17,18] that the ability of 5-HT to constrict rabbit coronary arteries is mediated by both 5-HT 1B and 5-HT 2A receptors. Our data also indicate that a mixed receptor population mediates contractile responses to 5-HT, including 5-HT 1B and 5-HT 2A receptors.…”
Section: Discussionmentioning
confidence: 97%
“…30,55,56 Enhanced 5-HT2AR expression was detected in arteries compared to veins and in the left coronary artery compared to the right coronary artery in rats and swine, respectively. 52,115 Interestingly, although AMI has been shown to facilitate transition of cardiac fibroblasts into myofibroblasts resulting in increased expression of SERT and TPH1, it does not result in any changes in 5-HT2AR expression in these myofibroblasts. 116 Pharmacological inhibition of 5-HT2AR activity showed cardioprotective effects with repressed hypertrophic remodeling.…”
Section: ■ 5-ht2rmentioning
confidence: 99%
“…More recently, Williams et al demonstrated that depressed cardiovascular patients have higher 5-HT2AR density on platelets and significantly higher incidence of major and minor cardiac adverse events . Moreover, 5-HT2AR-mediated signaling can regulate the vascular tone leading to vasoconstriction. ,, Enhanced 5-HT2AR expression was detected in arteries compared to veins and in the left coronary artery compared to the right coronary artery in rats and swine, respectively. , Interestingly, although AMI has been shown to facilitate transition of cardiac fibroblasts into myofibroblasts resulting in increased expression of SERT and TPH1, it does not result in any changes in 5-HT2AR expression in these myofibroblasts …”
Section: -Ht2rmentioning
confidence: 99%
See 1 more Smart Citation